Talking delicately: Providing opportunistic weight loss advice to people living with obesity - Madeleine Tremblett; Helena Webb; Sue Ziebland; Elizabeth Stokoe; Paul Aveyard; Charlotte Albury (Elsevier, 2022)
Obesity is a major worldwide public health problem. Clinicians are asked to communicate public health messages, including encouraging and supporting weight loss, during consultations with patients living with obesity. However, research shows that talking about weight with patients rarely happens and both parties find it difficult to initiate. Current guidelines on how to have such conversations do not include evidence-based examples of what to say, when to say it and how to avoid causing offence (a key concern for clinicians). To address this gap, we examined 237 audio recorded consultations between clinicians and patients living with obesity in the UK in which weight was discussed opportunistically. Conversation analysis revealed that framing advice as depersonalised generic information was one strategy clinicians used when initiating discussions. This contrasted to clinicians who made advice clearly relevant and personalised to the patient by first appraising their weight. However not all personalised forms of advice worked equally well. Clinicians who spoke delicately when personalising the discussion avoided the types of patient resistance that we found when clinicians were less delicate. More delicate approaches included forecasting upcoming discussion of weight along with delicacy markers in talk (e.g. strategic use of hesitation). Our findings suggest that clinicians should not avoid talking about a patient's weight, but should speak delicately to help maintain good relationships with patients. The findings also demonstrate the need to examine communication practices to develop better and specific guidance for clinicians. Data are in British English.